CIM implementation of the molding shop floor in a manufacturing plant - Khor, Karen Jor Wei. (2008)
Ideas of lean production technology, stripped-down management, worker empowerment, flexible customized manufacturing, and other modern strategies, are coming together to create a new kind of corporation and a worldwide business revolution. While many American, Japanese, and European companies have discovered that the key to improved competitiveness, is through redesigning their businesses and their business relationships, thus resulting in extraordinary gains for these companies; a number of corporations have their market share lost by clinging to outmoded thinking.